2007
DOI: 10.1016/j.physletb.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-out volume of hot dense fireball

Abstract: A thermodynamically consistent excluded volume model is proposed to account for the particle multiplicities obtained from lowest SIS energies to the highest RHIC energies. The chemical freeze-out volumes lying in a slice of one unit of rapidity for pions and kaons are separately inferred from this analysis and the results are compared with the corresponding thermal freeze-out volumes obtained from the Hanbury-Brown Twiss (HBT) pion interferometry. Furthermore, we extract the variations of freeze-out number den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…Moreover, at GSI-SIS and BNL-AGS energies, the freeze-out parameters involve a much larger values of baryon chemical potentials and the predictions of all the excluded-volume models are quite different from those obtained in the ideal gas models. We have already shown the utility of the present model in explaining various properties of hot, dense hadron gas [11,12]. The analysis presented here lends further support to our claim that the excluded-volume model obtained by us properly explain the multiplicities and particle ratios of various particles after chemical freeze-out.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, at GSI-SIS and BNL-AGS energies, the freeze-out parameters involve a much larger values of baryon chemical potentials and the predictions of all the excluded-volume models are quite different from those obtained in the ideal gas models. We have already shown the utility of the present model in explaining various properties of hot, dense hadron gas [11,12]. The analysis presented here lends further support to our claim that the excluded-volume model obtained by us properly explain the multiplicities and particle ratios of various particles after chemical freeze-out.…”
Section: Discussionsupporting
confidence: 86%
“…Recently we have given a model based on the geometrical excluded volume correction which describes suitably the thermodynamical quantities of a hot and dense HG [11]. We have further used this prescription to determine the freeze-out volume of the fireball as well as pions and nucleon density [12]. We find that the densities are reproduced well by their HBT experimental data.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is also encouraging to see that its predictions on various quantities are completely in agreement with those given by a simulation model [14] involving microscopic details of the collision geometry and the multiple scattering algorithm. We have also found that our model predicts meson and baryon densities in excellent agreement [15] with the data obtained from the analysis of the pion interferometry (HBT) [16]. In this paper we have evaluated the fireball volume at chemical freeze-out and the extremely large value of the fireball volume indicates the existence of a mixed phase between the QGP to HG phase transition [15].…”
Section: Introductionsupporting
confidence: 75%
“…We have also found that our model predicts meson and baryon densities in excellent agreement [15] with the data obtained from the analysis of the pion interferometry (HBT) [16]. In this paper we have evaluated the fireball volume at chemical freeze-out and the extremely large value of the fireball volume indicates the existence of a mixed phase between the QGP to HG phase transition [15]. These results make it amply clear that our excluded volume model can provide a reasonable description of the EOS of HG produced in the heavy-ion collisions from the lowest SIS to the highest RHIC energy.…”
Section: Introductionsupporting
confidence: 69%